Anti Inflammatory and Antioxidant Activity of Ziziphus Jujuba Extract - Singh, Bhawana; Gautam, Sandra; Dubey, B K; Basedia, Deepak Kumar (Asian Journal of Pharmaceutical Research and Development, 2022)
The antioxidant activity of the leaves and fruits of Ziziphus jujuba and contribution in some phytochemical characteristics was obtained. Phytochemical analysis was found that Ziziphus jujuba leaves and Fruits were loss on drying 0.85%, 0.65%, total ash values were 5.3%, 7.6% , Acid insoluble ash value were 2.9%, 4.4%, Water soluble ash value were 0.7%, 1.1% and Foaming index were 13ml, 12ml. Phytochemical screening was found that carbohydrate present in JFE and JFA, alkaloids were present in JLE, JLA and JFE, glycosides were present in JFA, flavonoids were present in all type of extracts, steroids were present in only JLE and protein and amino acids were present in JFE and JFA. JFE possessed higher antioxidant activity with IC50 value of < 300 µg/ml among all extracts for both methods and higher inhibition found in DPPH method 96.32% and in ABTS method it is 98.68 %. Aqueous extract of Ziziphus Jujuba fruit (JFA) was exhibited excellent anti-inflammatory activity against COX-1 & Cox-2 with IC50 value less than <0.2mg/ml. Ethanolic extract of leaf (JLE) & Ethanolic extract of fruit (JFE) possessed moderate activity (< 0.3) against both COX-1 & Cox-2. Aqueous extract of leaf (JLA) exhibited poor activity against both COX-1 & Cox-2. Overall conclusion of anti-inflammatory study of different extracts of Ziziphus Jujuba leaves and fruit were possessed anti inflammatory activity and inhibition was increased with concentration of samples increased.